The course of COVID-19 in Jamaica from outbreak to vaccination - Kevoyne H Chambers (Caribbean Medical Journal)
Objective: To describe the incidence of confirmed COVID-19 cases and deaths in Jamaica and assess the country’s vaccination and prevention efforts. Methods: This study analyzed the daily number of new confirmed COVID-19 cases and deaths in Jamaica from March 2020 to February 2023 and showed how different factors influenced rate of new cases and deaths across the island. It also assessed Jamaica’s vaccination and prevention efforts from April 2021 to February 2023. Results: In this descriptive ecological study, two variables: the daily number of new confirmed cases and deaths were analyzed to describe the incidence of COVID-19 in Jamaica during the pandemic. Changes in COVID-19 policies by the Jamaican government as well as the characteristics of different COVID-19 variants corresponded to an increased number of new daily COVID-19 cases and deaths among the Jamaican population. Currently, only 29.97% of the Jamaican population has completed the initial COVID-19 vaccination protocol which ranks Jamaica 32 out of 33 countries in Latin America and the Caribbean as of February 10, 2023, when looking at the number of COVID-19 vaccination doses per 100 population. Conclusion: During the COVID-19 pandemic in Jamaica, the daily number of new confirmed cases and deaths corresponded to changes in COVID-19 policies and the characteristics of different COVID-19 variants. Jamaica needs to implement more strategies to increase the vaccination rate across the country.